2020
DOI: 10.1186/s12889-020-08715-4
|View full text |Cite
|
Sign up to set email alerts
|

The association between physical activity with incident obesity, coronary heart disease, diabetes and hypertension in adults: a systematic review of longitudinal studies published after 2012

Abstract: Background: A growing body of studies that investigated the longitudinal association between physical activity (PA) and the outcome of incident obesity, coronary heart disease (CHD), diabetes and hypertension has become available in recent years. Thus, the purpose of this systematic review was to provide an update on the association between PA and onset of obesity, CHD, diabetes and hypertension in individuals aged ≥18 years who were free of the respective conditions at baseline. Methods: We systematically sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
90
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(105 citation statements)
references
References 65 publications
9
90
0
6
Order By: Relevance
“…Yet, in contrast to the prevailing expectations, observational longitudinal studies suggest that higher adiposity at baseline is associated with lower physical activity and longer time spent sedentary at follow‐up, indicating that greater adiposity may lead to lower levels of physical activity 5–10 . Some, but fewer, longitudinal studies have suggested the opposite—expected—direction in the relationship, namely, a negative correlation between physical activity and weight gain after several years of follow‐up 11,12 . Inference of causal relationships between physical activity/sedentary behaviour and adiposity is limited by the nature of observational longitudinal studies with repeated assessments at single time points at fairly long intervals, before, during and after which the changes in the variables cannot be monitored.…”
Section: Introductionmentioning
confidence: 95%
“…Yet, in contrast to the prevailing expectations, observational longitudinal studies suggest that higher adiposity at baseline is associated with lower physical activity and longer time spent sedentary at follow‐up, indicating that greater adiposity may lead to lower levels of physical activity 5–10 . Some, but fewer, longitudinal studies have suggested the opposite—expected—direction in the relationship, namely, a negative correlation between physical activity and weight gain after several years of follow‐up 11,12 . Inference of causal relationships between physical activity/sedentary behaviour and adiposity is limited by the nature of observational longitudinal studies with repeated assessments at single time points at fairly long intervals, before, during and after which the changes in the variables cannot be monitored.…”
Section: Introductionmentioning
confidence: 95%
“…The simplest and most illustrative examples are: a) the in/out energy balance; and b) increased cardiorespiratory reserves. Regarding energy balance, PA-related energy expenditure would reduce the risk of obesity ( Cleven et al, 2020 ; Bell et al, 2014 ; Pavey et al, 2016 ); obesity is one of the most important risk factors for severe SARS-Cov-2 infections. For cardiorespiratory fitness, the SARS-Cov-2-associated hypoxemia pneumonia ( Yang et al, 2020 ) is a major clinical sign of the infection; it is therefore plausible to think exercise, which is highly associated with increased cardiorespiratory fitness, including among older adults ( Hurst et al, 2019 ), would reduce the risk of hypoxia and its deleterious effects because exercise increases cardiorespiratory reserves (improved heart and lung functioning), keeping infected individuals away from the cut-point below which low cardiorespiratory fitness is critical to help the organism fighting against the infection.…”
Section: Pa/exercise Severe Sars-cov-2 Infection and Gerosciencementioning
confidence: 99%
“…Diabetes is a noncommunicable disease and a major threat to economies and societies as identified by WHO. The management of diabetes is more costly in low‐ and middle‐income and emerging market countries [4, 5]. As an alternative, the emphasis on phytochemicals [6] and herbal products [7] provide cost‐effective strategies to combat diabetes.…”
Section: Introductionmentioning
confidence: 99%